The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2528/pierc22072508
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Millimeter Wave SIW Slotted Array Antenna

Abstract: A high performance substrate integrated waveguide (SIW) slotted array antenna with low sidelobe level and optimum gain at 28 GHz is designed, and experimental results are presented with simulated data. In order to achieve a low sidelobe level, Chebyshev power coefficients in the form of slot displacements are applied to the SIW array antenna. A MATLAB program has been written to find these slot displacements. This work entails investigating and designing the optimum microstrip to SIW transition over the Ka-ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…In this section, we present the realization of a slot array from a single element to achieve gain enhancement. As the number of slot elements increases, the gain of the array increases [25,26]. Initially, a two-element (2 × 1) substrate integrated waveguide (SIW) array is introduced, demonstrating improved gain compared to a single element.…”
Section: Siw Array Realizationmentioning
confidence: 99%
“…In this section, we present the realization of a slot array from a single element to achieve gain enhancement. As the number of slot elements increases, the gain of the array increases [25,26]. Initially, a two-element (2 × 1) substrate integrated waveguide (SIW) array is introduced, demonstrating improved gain compared to a single element.…”
Section: Siw Array Realizationmentioning
confidence: 99%
“…T here has been very active research on substrate integrated waveguide solutions in recent years due to their manufacturing simplicity in printed circuit board (PCB) technology and low losses. Their applications span waveguiding structures [1], antennas [2], microwave circuits including power dividers [3,4], baluns [5,6], and filters [7]. There are also efforts to integrate them with electronics [8,9] for lower losses at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers have shown that the SIW has the same working principle and propagation characteristics as that of RWG (Cassivi et al , 2002; Xu et al , 2003; Xu and Wu, 2004; Yan et al , 2005; Xu and Wu, 2005). In 2022, Kunooru et al , have designed a high-performance rectangular slotted array antenna at 28 GHz for mm-waves using MS line to SIW transition (Bharath et al , 2022). Kim M. et al , have proposed an MS-to-SIW transition using a balanced/single slot for mm-wave from the 15–40 GHz band.…”
Section: Introductionmentioning
confidence: 99%